Pengaruh Pengetahuan Dewan Tentang Anggaran Terhadap Pengawasan Keuangan Daerah - Ulil Abshar; Wiyana, Anim (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine the effect of council knowledge about the budget on regional financial supervision at the Regional People's Representative Council Office in Makassar city. In this study, researchers examined the Regional Financial Supervision in the Regional People's Representative Council of Makassar City using an independent variable, namely, the council's knowledge of the budget. The population in this study is all members of the Regional People's Representative Council of Makassar city. Sampling was carried out using the Purposive Sampling method, with a sample of 50 respondents. The data collection method uses primary data obtained from the distribution of questionnaires. The data analysis technique used in this study is a simple regression analysis technique. The results stated that the council's knowledge of the budget had a positive effect on regional financial supervision.